Lin May Saeed and Post-Anthropocentric Art: Review of Robert Wiesenberger et al., Lin May Saeed: Arrival of the Animals - Herman, David (Humanimalia, 2023)
Robert Wiesenberger. Lin May Saeed: Arrival of the Animals, with contributions by Mel Y. Chen, Lin May Saeed, and Birgit Mütherich. Ex. cat. Williamstown, MA: Clark Art Institute; New Haven, CT: Yale University Press, 2020. 144 pp.; 70 colour ill. 35 (paper).